2020
DOI: 10.13102/sociobiology.v67i4.5860
|View full text |Cite
|
Sign up to set email alerts
|

Soundscape Indices: New Features for Classifying Beehive Audio Samples

Abstract: As the study of honey bee health has gained attention in the biology community, researchers have looked for new, non-invasive methods to monitor the health status of the colony. Since the beehive sound alters when the colony is exposed to stressors, analysis of the acoustic response of the colony has been used as a method to identify the type of stressor, whether it is chemical, pest, or disease. So far, two feature sets have been successfully used for this kind of analysis, being these low-level signal featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Research by Sharif (2020) has shown that the sound of beehives can be in uenced by volatile chemical compounds in the air, such as acetone, ethyl ether, glutaric dialdehyde and trichloromethane. In addition, these changes can be identi ed by the ML model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research by Sharif (2020) has shown that the sound of beehives can be in uenced by volatile chemical compounds in the air, such as acetone, ethyl ether, glutaric dialdehyde and trichloromethane. In addition, these changes can be identi ed by the ML model.…”
Section: Discussionmentioning
confidence: 99%
“…Cejrowski et al (2020) also presented a method that uses Mel Frequency Cepstral Coe cients (MFCCs) features and an SVM classi er to de ne the start and the end of the presumed bees-night in summer. In addition to MFCCs, soundscape indices are considered to be a valid set of features for acoustic analysis of a beehive, and call the attention of research community to further employ them in bioacoustics-related investigations (Sharif et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of digital sound recordings and the extraction of the Acoustic Indices (AI) [80] have been used for Rapid Biodiversity Assessment (RBA) [81] in an increasing rate for a variety of environments [82][83][84]. Furthermore, the scientific field of ecoacoustics [85,86] has offered a new approach regarding the investigation of the ecological role of sound [87][88][89][90].…”
Section: Ecological Acoustics Approach Methodologymentioning
confidence: 99%
“…Acute and chronic oral administration of ultrapure TiO 2 particulate matter to adult bees altered the bee microbial community; therefore, airborne particulate matter may represent an additional risk factor for honeybee health, promoting sublethal effects against the gut microbiota [ 216 ]. The second most recent paper was a work by Sharif et al [ 217 ] that, by looking for new, non-invasive methods to monitor the health status of the colony, introduced new features for classifying beehive audio samples using the soundscape indices [ 217 ]. In 2021, Nicewicz et al [ 218 ] outlined the antioxidant capacity of honey from an urban apiary and honey from a rural apiary [ 218 ].…”
Section: Nutritional Value Bioactive Components and Beneficial Properties Of Bee Productsmentioning
confidence: 99%